Lithospheric Thermal Structure in Jinggangshan City: Implications for High Geothermal Background - Liao, Yuzhong; Liu, Yanguang; Liu, Feng; Wei, Shuaichao; Duan, Hexiao (Frontiers in Earth Science, 2022)
The Jinggangshan city is located in the southwest of the Jiangxi province that is enriched in hot spring. However, few geothermal research has been conducted here, which limits the exploration and utilization of the geothermal resource. In this study, we carried out well logging, analyses of rock thermal conductivity and heat production to estimate the terrestrial heat flow. Combining the surrounding science transect and Crust 1.0 model, the one-dimension lithospheric thermal structure was constructed by solving steady-state heat conduction equation. Furthermore, the deep temperature distribution has been obtained for a better understanding of the geodynamic condition of the geothermal resource. The results show that the heat flow in the study area is as high as 83.52 m·W·m-2, implying the high heat background for the formation of the geothermal source. According to the lithospheric thermal structure of the Jinggangshan city, the mantle contributes (qm/qc > 1) more than the crust to the terrestrial heat flow. The temperature of the Moho surface is 671.7 °C, consistent with the Moho temperature (620-690 °C) below the Tancheng-Lujiang deep fault. Meanwhile, the calculated depth of Curie surface (585 °C) is 27 km, in accordant with the depth of Curie isotherm estimated based on aeromagnetic data. The consistence of the Curie surface depth verifies the validity of the lithospheric thermal structure constructed for the Jinggangshan city. In general, the high heat background plays an important role in the formation of the geothermal resource in the Jinggangshan city.